Processing of the acoustic wave image - DRZEWIECKA, Maria Anna; SZUSTAKOWSKI, Mieczysław (Archives of Acoustics, 1982)
This paper presents investigations of a system for processing the image of acoustic wave generated in transparent media. It also gives an analysis of the system and discusses the influence of parameters of spatial filtre apertures and of the acoustic field on the quality of representation of the field intensity distribution.